Role of Blockchain Technology in Health Record Management - Shivani Pramod Gupta; Keshav Kumar (International Journal of Information Security Engineering, 2024)
Maintaining thorough medical records is essential to raising a healthy population in the fast-paced world of global development. Intimidating data breaches have been the consequence of the traditional centralized strategy to maintaining health records, yet it has proven vulnerable. The 2017 Ponemon Cost of Data Breach Study estimated that each compromised healthcare record could incur a significant cost of approximately $380. Regrettably, the 2016 Breach Barometer Report revealed that case records have been compromised. A mindset shift is necessary in order to admit the limitations of institution-driven record conservation. Individualities under the present models are not empowered, which makes their sensitive data vulnerable to abuse. Thus, a radical, decentralized, and case-centered approach is needed, one that gives the patient complete power. Blockchain technology provides a game-changing answer ready to take on these problems head on. The problems of conventional record-keeping are greatly reduced in a decentralized and distributed tally system like blockchain. Piecemeal from mollifying data breaches, blockchain holds the capability to transfigure other aspects of the healthcare assiduity, similar as billing procedures, safe record-sharing, progress in medical exploration, and a strong hedge against identity theft and fiscal data crimes. A fresh position of complexity has been added with the preface of smart contracts, which streamline operations by automating processes like record creation, confirmation, and incantation directly on the blockchain. By exercising blockchain technology, the healthcare assiduity can guarantee the confidentiality of patient data and pave the path for a day when patient autonomy, data security, and openness are of utmost significance. This creative strategy not only protects people's health but also ushers in a new period of effectiveness and confidence for the healthcare sector. In addition to utilizing blockchain technology, this paper suggests integrating smart contracts into a patient-driven healthcare record system. A revolutionary effect on healthcare data management is predicted, and it highlights the need for additional study and real-world application.
Keywords: blockchain; cryptographic hash; decentralization; immutability; smart contract